Critical care nurses’ knowledge regarding prevention of central venous catheter-related infection in Saudi Arabia: A cross-sectional study - Bassam Shyhan Alshammari; Salman Hamdan Alsaqri; Sameer A. Alkubati; Jordan H. Llego; Ahmad K. Al-Sadi; Aziza Z. Ali; Wessam A. Elsayed; Anas Mahmoud Balawi; Shaimaa Mohamed Nageeb; Laila A. Hamed (Belitung Nursing Journal)
Background: Central venous catheter-related infections (CVC-RIs) are a significant concern in intensive care units (ICUs), contributing to increased morbidity, mortality, and healthcare costs. Nurses play a crucial role in preventing these infections through proper catheter care, adherence to aseptic techniques, and early detection of complications. However, knowledge gaps may hinder effective infection prevention and patient outcomes.